Pengaruh Pemberian Ekstrak Daun Ara Sungsang (Asystasia gangetica) Terhadap Jumlah Sel Fibroblas pada Mencit (Mus musculus) yang Mengalami Luka Sayat (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2023)
Chinese violet is a type of herbaceous plant that is widely used in medication. Chinese violet has anti-inflammatory, analgesic and antimicrobial properties. This plant can be used in incision wounds. This study aims to analyze the effect of chinese violet leaf extract on the number of fibroblast cells of mice that experienced incision wounds. Experimental research was conducted using a completely randomized design method on 25 male mice weighing 20-50 grams. The research group was divided into five, namely K1 as a negative control (aquades), K2 as a positive control (povidone iodine), K3 as much as 5% of breech fig leaf extract, K4 as much as 10% of breech fig leaf extract, and K5 as much as 15% of fig leaf extract breech. The incision was made using a scalpel with a length of 2 cm and a depth of ± 2 mm. Data were analyzed using ANOVA with α = 0.05 and the LSD follow-up test. The results showed that the highest average increase in the number of fibroblast cells was found in treatment K4 (40.88) close to K2 (41.36), followed by K5 (40.04), K3 (38.64) and K1 (22.64) . The results of this study can be concluded that the breech chinese violet fig extract has a significant effect on the number of fibroblast cells.